Fight for Your Right to Fruit: Psychosocial Outcomes of a Manga Comic Promoting Fruit Consumption in Middle-School Youth. Issue 5 (4th May 2017) - Leung, May May; Green, Melanie C.; Tate, Deborah F.; Cai, Jianwen; Wyka, Katarzyna; Ammerman, Alice S.
ABSTRACT: The purpose of this study was to determine whether exposure to a manga comic (Japanese comic art) with messages promoting fruit consumption influenced psychosocial variables associated with increased fruit intake in middle-school youth. A three-group, randomized, single-session study was conducted in two public middle schools in central North Carolina. Participants were randomly assigned to one of three groups: (a) comic ( manga comic promoting fruit consumption, (b) newsletter (newsletter about fruit), or (c) attention-control (newsletter about ancient Greece). Participants included N = 263 youth, with a mean age of 13.18 years ( SD = 1.12). Outcome expectations, self-efficacy, and knowledge related to fruit intake were measured at baseline and immediately after reading. Secondary outcomes included transportation (degree to which participants are immersed in their media) and enjoyment, measured at posttest. Data were analyzed using regression analyses. Comic group participants tended to have greater change in outcome expectations related to fruit intake compared to the attention-control group and greater transportation and enjoyment than the newsletter and attention-control groups. Study results are promising and suggest that manga comics may be a useful format to promote positive health beliefs in youth.